2003
DOI: 10.1002/jbm.a.10042
|View full text |Cite
|
Sign up to set email alerts
|

In vitro release kinetics of proteins from bioactive foams

Abstract: This study describes an approach to obtaining 3-D scaffolds for tissue engineering that allows the incorporation and release of biologically active proteins to stimulate cell function. Laminin was adsorbed on the textured surfaces of binary 70S30C (70 mol % SiO(2), 30 mol % CaO) and ternary 58S (60 mol % SiO(2), 36 mol % CaO, 4 mol % P(2)O(5)) foams. The covalent bonds between the binding sites of the proteins and the ligands on the scaffolds' surfaces did not denaturate the proteins. In vitro studies show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Note that the optimal concentration of ionic products of dissolution, especially the silicate and Ca 2 + ions released from a BG surface, is important for bone regeneration. 3 On the other hand, proteins can bond to the BG surface, 58 and thus mediate cell attachment, migration, and growth. 29 These surface area-regulated protein absorption and ion release processes can greatly affect the performance of a biomaterial.…”
Section: The Role Of Nanopore Topology On Cell Responsementioning
confidence: 99%
“…Note that the optimal concentration of ionic products of dissolution, especially the silicate and Ca 2 + ions released from a BG surface, is important for bone regeneration. 3 On the other hand, proteins can bond to the BG surface, 58 and thus mediate cell attachment, migration, and growth. 29 These surface area-regulated protein absorption and ion release processes can greatly affect the performance of a biomaterial.…”
Section: The Role Of Nanopore Topology On Cell Responsementioning
confidence: 99%
“…Sol-gel glasses can then easily be functionalised with groups such as mercapto-and amino-groups 24 that can be used to covalently bond proteins to the surface of the glasses. 25 Specific nanopore shapes and sizes may also affect which proteins are adsorbed to the glass surface. This can be used in a variety of applications.…”
Section: Sol-gel Derived Bioactive Glass Foam Scaffoldsmentioning
confidence: 99%
“…1,2,16 The hierarchical structure of the bioactive foams can be tailored for tissue bonding, resorption and delivery of dissolution products that provide the controlled rates of release of osteogenic stimuli, [68][69][70] and the nanopores can be modified with various proteins to control cell integrin-scaffold interactions. 71,72 The calcia-silica-based materials are easily and economically processed to ISO standards 69 and have been used clinically for 20 years with FDA and CE regulatory clearance. Our studies have shown that the inorganic ionic dissolution products released during controlled resorbtion of the gel-glass scaffolds stimulate expression of genes and enhance osteogenesis in mouse and human ES cells, 16 adult human stem cells 1 and human foetal bone cells.…”
Section: 67mentioning
confidence: 99%